A modified Delphi process to establish future research priorities in malignant oesophagogastric surgery. Issue 6 (December 2020) - Wilson, Michael SJ.; Blencowe, Natalie S.; Boyle, Christopher; Knight, Stephen R.; Petty, Russell; Vohra, Ravi S.; Underwood, Tim J.; ,
Abstract: Background: With rapid advancement in the genomics of oesophagogastric (OG) cancer and raised expectations in clinical outcomes from patients and clinicians alike there is a clear need to determine the current research priorities in OG cancer surgery. The aim of our study was to use a modified Delphi process to determine the research priorities among OG cancer surgeons in the United Kingdom. Methods: Delphi methodology may be utilised to develop consensus opinion amongst a group of experts. Members of the Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland were invited to submit individual research questions via an online survey (phase I). Two rounds of prioritisation by multidisciplinary expert healthcare professionals (phase II and III) were completed to determine a final list of high priority research questions. All questions submitted and subsequently ranked were analysed on an anonymised basis. Results: In total, 427 questions were submitted in phase I and 75 with an OG cancer focus were taken forward for prioritisation in phase II. Phase III produced a final list of 12 high priority questions with an emphasis on tailored or personalised treatment strategies in OG cancer surgery. Conclusion: A modified Delphi process produced a list of 12 high priority research questions in OG cancer surgery. Future studies and awards from funding bodies should reflect this consensus list of prioritised questions in the interest of improving patient care and encouraging collaborative research across multiple centres.